Pembuatan Logo dan Kemasan untuk Pengembangan Nilai Ekonomis Produk UMKM Sumba Timur - Alfrian C Talakua; Dessy Asnath Sitaniapessy; Sri Rani; Danial Umbu Hiwa; Janwward Bunga Kale; Semi Tungga Haluwalu; Anggreni Anggreni; Putra Kurniawan (Jurnal Pengabdian Masyarakat (abdira), 2022)
Service activities are aimed at micro, small and medium enterprises or UMKM located in East Sumba. The problem is the lack of understanding in marketing and promoting products so that it’s difficult to develop, this is the main reason for implementing this activity. The implementation of the graphic design field is needed to help produce logos and packaging as identities that help increase the selling value of the product. Service activities were carried out on 3 UMKM in Waingapu, East Sumba, in this activity the team provided socialization related to the use of technology for marketing and produced logo designs and product packaging that had reached the copyright registration stage to be developed into local brands. The results of this activity are expected to help the marketing process and product development. A good response was received by the team with a satisfaction percentage of 75% Very Satisfied, 20% Satisfied and 5% Quite Satisfied.